VaxArray potency assay for rapid assessment of "pandemic" influenza vaccines. (December 2018) - Byrne-Nash, Rose; Miller, David; Bueter, Katie; Gillis, Jacob; Kuck, Laura; Rowlen, Kathy
Abstract The VaxArray Influenza Pandemic HA (VXI-pHA) potency assay is a multiplexed sandwich immunoassay that consists of nine broadly reactive yet subtype-specific monoclonal capture antibodies printed in microarray format and a suite of fluor-labeled secondary antibodies that were selected to probe conserved HA epitopes. VXI-pHA was designed to optimize the probability that the ready-to-use assay would work for the most concerning, emergent influenza A strains, eliminating the need for the time-consuming process of reference reagents production. The performance of this new potency test was evaluated using a panel of 48 potentially pandemic strains of influenza viruses and vaccines spanning 16 years of antigenic drift, including the most recent pre-pandemic vaccine being developed against the "5th wave" A/H7N9 virus. The VXI-pHA assay demonstrated coverage of 93%, 92%, and 100% for H5, H7, and H9 antigens, respectively. The assay demonstrated high sensitivity with linear dynamic ranges of more than 150-fold and quantification limits ranging from 1 to 5 ng/mL. For three production lots of H7N9 monobulk drug substance, the assay exhibited excellent accuracy (100 ± 6%) and analytical precision (CV 6 ± 2%). The high assay sensitivity enabled robust detection and quantification of hemagglutinin in crude in-process samples and low-dose, adjuvanted vaccines with an accuracy of 100 ± 10%. Vaccines potency: A new specific assay for potential pandemic influenza Potency of inactivated influenza vaccines is determined based on the viral hemagglutinin (HA) content in the vaccine preparation. Specific assays need to be rapidly available to avoid a delay for pandemic vaccine production. In this study, led by Kathy Rowlen, researchers from InDevR in Colorado developed an immunoassay for potency testing of pandemic influenza vaccines. The VaxArray assay utilizes a panel of monoclonal antibodies and recognizes 94% of the tested H5, H7, and H9 antigens representing 16 years of circulating influenza viruses. VaxArray shows high specificity for the tested HAs and recognizes only correctly folded HA antigen, which is crucial to accurately determine vaccine potency. Furthermore, the assay displays high sensitivity and accuracy, even for crude in-process samples containing contaminants from production or for low dose, adjuvanted samples. The combination of broad reactivity and high specificity for potentially pandemic HAs makes VaxArray a promising tool for pandemic preparedness.